Determinants of Initial Satisfaction with the Succession Process in Family Firms: A Conceptual Model - Sharma, Pramodita; Chrisman, James J.; Pablo, Amy L.; Chua, Jess H. (Entrepreneurship Theory and Practice, 2001)
Leadership succession continues to form the core of the family business literature. Numerous studies have suggested factors that influence family members' initial satisfaction with the succession process, but this body of work is highly fragmented and lacks a unifying framework. In this paper, we draw on stakeholder theory and other organizational, behavioral, and economic theories to develop a conceptual model that integrates the findings from the literature. The research and practical implications of this integrative, ready-to-test, model are discussed.